Healthcare professionals’ knowledge, attitude and practice towards National Centralized Drug Procurement policy in central China: A cross-sectional study - Huang, Anqi; Wang, Xuanxuan; Tao, Yun; Lin, Likai; Cheng, Hong (Frontiers in Pharmacology, 2022)
Background: National Centralized Drug Procurement (NCDP), an ongoing government-led policy starting in 2019 in China, aimed at reducing drug costs. During the implementation of NCDP, healthcare professionals (HCPs) still have a certain degree of concern about the policy, which affects the clinical use of related drugs. Objective: This study aims to assess the level of knowledge, attitude and practice (KAP) of HCPs towards NCDP policy, together with the associated factors that determine their KAP. Methods: A cross-sectional study was conducted between September and November of 2021 in 30 hospitals in Hubei province in Central China. A self-designed online questionnaire including KAP towards NCDP policy was administered to HCPs. Logistic regression analysis was adopted to identify the factors associated with KAP. Results: A Total of, 742 HCPs completed the questionnaires. 43.4% of HCPs had good knowledge, 24.7% had a positive attitude, and 23.7% held good practice. Through multivariate logistic regression analysis, HCPs who are males, pharmacists, with senior professional titles and 6–10 years of professional working experience contributed to a higher knowledge level. Pharmacists and HCPs with good knowledge were more likely to have positive attitudes, while HCPs with higher education were less likely to have positive attitudes. Pharmacists, HCPs who had 11–20 years of professional working experience, worked in medium-size urban areas or had good knowledge were more likely to have good practice. Good practice is also associated with the positive attitude towards the efficacy of centralized-purchased medicines and impacts of NCDP policy. Conclusion: Only a small percentage of HCPs had good KAP towards NCDP policy. Pharmacists showed better KAP than physicians. The positive attitude towards the efficacy of centralized-purchased medicines and impacts of NCDP policy contributed to better practice. High-quality clinical evidence on the therapeutic effects and safety of the centralized-purchased drugs is needed.